2023
DOI: 10.1002/nop2.1656
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐role nurse interpreter perceptions of language barriers and Spanish‐speaking patients: A qualitative study

Abstract: Aim As the United States population is ever changing and is growing in diverse population patterns, the health care system is called to initiate responsive health care practices that are based on the public's changing and diverse cultural patterns. This study sought to explore the perceptions of certified medical interpreter dual‐role nurses and their experiences with Spanish‐speaking patients from admission to discharge in hospital stays. Design A qualitative descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…8 Hispanic adults' satisfaction with the provision of health information seems to be related to practitioners' cultural competency, including their regard for patients' language preference. 9,10 A study of 25 Spanish-speaking Latino adults' perspectives of communication within healthcare found that participants believed English-speaking patients were treated better by practitioners than those who spoke Spanish. 11 Participants reported that inaccurate translations led to unintended healthcare consequences and financial hardships, resulting in inequity in stroke systems of care for Spanish-speaking Hispanic and Latino (SSH/L) adults.…”
Section: Introductionmentioning
confidence: 99%
“…8 Hispanic adults' satisfaction with the provision of health information seems to be related to practitioners' cultural competency, including their regard for patients' language preference. 9,10 A study of 25 Spanish-speaking Latino adults' perspectives of communication within healthcare found that participants believed English-speaking patients were treated better by practitioners than those who spoke Spanish. 11 Participants reported that inaccurate translations led to unintended healthcare consequences and financial hardships, resulting in inequity in stroke systems of care for Spanish-speaking Hispanic and Latino (SSH/L) adults.…”
Section: Introductionmentioning
confidence: 99%